Evolution of the beetle hind wing, with special reference to folding (Insecta, Coleoptera) - Fedorenko, Dmitri N. (Pensoft, 2009)
The present monograph is a highly original and thorough attempt at revising the wing structure of the beetles, with special emphasis placed not only on the venation patterns observed, but also on folding. Combined, all of these patterns are critically re-evaluated to provide new, highly unorthodox insights in beetle evolution. The work is also abundantly illustrated by original drawings showing all the necessary details of beetle wing structure, including shape, venation, sclerotization and folding patterns. The present monograph is indispensable for students in beetle taxonomy, evolution and palaeontology. Dr. Dmitri Fedorenko, born 1962, is Senior Scientist at the Institute of Ecology and Evolution, Russian Academy of Sciences, Moscow. His main interests lie in the taxonomy, ecology, geography and evolution of the beetles, the ground-beetles in particular. He is the author of more than 40 scientific papers, including the monograph "Reclassification of world Dyschiriini, with a revision of the Palearctic fauna (Coleoptera, Carabidae)", Moscow-Sofia-St. Petersburg: Pensoft Publishers, 1996.